How can smart technologies be applied by smallholder farmers for increased productivity and sustained livelihoods? - Booi, Samkelo Lutho (Department of Information Systems, 2022)
Problem Statement: The world population is expected to rapidly increase, raising food security concerns across the world. This will impact Africa most severely. The use of innovative farming techniques and technology has proven to accelerate the production yields and improve resilience to vulnerabilities which impact agricultural productivity. The use of smart technologies in farming is mainly present among largescale commercial farms, with minimal representation in the smallholder farming sector. On the other hand, a substantial amount of food in developing countries is produced by small scale farmers. Research Objective: The purpose of the study is to investigate the usage of smart technologies by smallholder farmers in South Africa, and to establish how smart technology could support smallholder farmers in increasing productivity through a three-dimensional view that takes into consideration capital, labour, and land utilization. To this end, an interpretive research philosophy was adopted. Research Design: The study collected the data using semi-structured interviews. The sample for the study constituted of 10 smallholder farmers and 12 subject matter experts within the agriculture and technology domain. To strengthen rigour within the study, the interviews were supported by documents containing viewpoints about how technology is applied in the African context and how it may be introduced and ultimately applied in the South African context. The study employed a deductive approach to theory, applying the Sustainable Livelihoods Approach (SLA) as theoretical underpinning for the study. SLA consists of a pentagon of livelihood assets: physical, social, human, natural, and financial assets. The framework was extended to include technology as an asset due to its potential to contribute to improving the livelihoods of smallholder farmers. Findings: The study found minimal to no use of smart technologies by smallholder farmers in South Africa. The factors which limited the use of technology include PEST (Political, Environmental, Social and Technological) factors. To achieve successful usage of smart technologies, collaboration is required from government, the private sector, smallholder farmers, and communities. Research Contribution: The study aimed to expand on the limited literature on the use of smart farming in the context of smallholder farmers in a developing country context. In addition, it contributed to extending the pentagon of livelihoods to include smart technologies with respect to smallholder farmer livelihoods. Therefore, the findings of this study contributed to the broader body of knowledge. In addition, insights from this study may be gained by the Department of Agriculture, Forestry and Fisheries, smallholder farmers, agricultural entrepreneurs and technologists in formulate developmental strategies and policies to improve the productivity of smallholder farmers as well as their livelihoods as a strategy to increase their contribution to food security in Africa while alleviating household poverty.